If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6r + -4r + 2 = 5r + -1r Reorder the terms: 2 + 6r + -4r = 5r + -1r Combine like terms: 6r + -4r = 2r 2 + 2r = 5r + -1r Combine like terms: 5r + -1r = 4r 2 + 2r = 4r Solving 2 + 2r = 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 2 + 2r + -4r = 4r + -4r Combine like terms: 2r + -4r = -2r 2 + -2r = 4r + -4r Combine like terms: 4r + -4r = 0 2 + -2r = 0 Add '-2' to each side of the equation. 2 + -2 + -2r = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2r = 0 + -2 -2r = 0 + -2 Combine like terms: 0 + -2 = -2 -2r = -2 Divide each side by '-2'. r = 1 Simplifying r = 1
| 10(t-5)+4t=7(2t+5)-12 | | ix^2-4x-4i=0 | | 6+9y+7=-8-(-6) | | 0=2x^3+v^2+4v+14 | | 2-5x=2x+9 | | 24-12x= | | 35x+7=36x+42 | | 23+x=26 | | S+2=9 | | x^3-3x=9.8 | | 8*w*2w= | | 71=-9+8x | | 19+2x=79 | | 7c*3e= | | (2*11)-(2*x)= | | (-5)3/(-5)3= | | 16-y=3y-8 | | 10=2p+2 | | 56-7x= | | Z-15=31 | | 2.8(3-2x)+3.2x=6.3-2(x-1.4) | | (8r-1)(5+2r)=(4r+5) | | x+y+39=36 | | (8r-1)(5+2r)=(4r+5)2 | | x/10=10/20 | | 1.06(53+x)=83+x | | 99-11x= | | 15x-3=5x-43 | | 1.7x+-1.62x=0.4x-0.32+8 | | 2k-5=10 | | 3x^2+14x-27=0 | | 14m^2-23m+8=0 |